For this case we must find the quotient of the following expression:
![\frac {\frac {x} {x-1}} {\frac {1} {x + 1}}](https://tex.z-dn.net/?f=%5Cfrac%20%7B%5Cfrac%20%7Bx%7D%20%7Bx-1%7D%7D%20%7B%5Cfrac%20%7B1%7D%20%7Bx%20%2B%201%7D%7D)
Applying double C we have the following expression:
![\frac {x (x + 1)} {x-1} =](https://tex.z-dn.net/?f=%5Cfrac%20%7Bx%20%28x%20%2B%201%29%7D%20%7Bx-1%7D%20%3D)
Applying distributive property to the terms within the parentheses of the numerator we have:
![\frac {x ^ 2 + x} {x-1}](https://tex.z-dn.net/?f=%5Cfrac%20%7Bx%20%5E%202%20%2B%20x%7D%20%7Bx-1%7D)
Thus, the quotient is given by option A
Answer:
Option A
Answer:
y = 2
Step-by-step explanation:
-y = 2, that means y = opposite of 2, which is -2
<em>Hope that helps! :)</em>
First, you add 1 to both sides. Then square both sides to get rid of the square root. After that you just solve it like a normal equation when you are left with 4x-2=9.
Answer:
The answer is 4/5
Step-by-step explanation:
#Hope it helps uh.....
Step-by-step explanation:
Describe how the values of a and k affect the graphical and tabular representations of the functions y=ax^2, y=x^2+k, and y=ax^2+k.